Circular RNA POSTN Promotes Myocardial Infarction-Induced Myocardial Injury and Cardiac Remodeling by Regulating miR-96-5p/BNIP3 Axis - Cheng, Nan; Wang, Ming-Yan; Wu, Yuan-Bin; Cui, Hui-Min; Wei, Shi-Xiong; Liu, Bing; Wang, Rong (Frontiers in Cell and Developmental Biology, 2021)
Myocardial infarction (MI) is the most prevalent cardiac disease with high mortality, leading to severe heart injury. Circular RNAs (circRNAs) are a new type regulatory RNAs and participate in multiple pathological cardiac progression. However, the role of CircRNAs Postn (CircPostn) in MI modulation remains unclear. Here, we aimed to explore the effect of CircPostn on MI-induced myocardial injury and cardiac remodeling. We identified that the expression of CircPostn was elevated in the plasma of MI patients, MI mouse model, and hypoxia and reoxygenation (H/R)-treated human cardiomyocytes. The depletion of CircPostn significantly attenuated MI-related myocardium injury and reduced the infarct size in MI mouse model. The CircPostn knockdown obviously enhanced left ventricular ejection fraction (LVEF) and left ventricular fraction shortening (LVFS) and inhibited left ventricular anterior wall thickness at diastole (LVAWd) and left ventricular posterior wall thickness at diastole (LVPWd). The depletion of CircPostn was able to decrease MI-induced expression of collagen 1α1 and collagen 3α1 in the ventricular tissues of the mice. The protein expression of collagen and α-SMA was up-regulated in the MI mice was inhibited by CircPostn knockdown. Meanwhile, the expression of ANP and BNP was repressed by the CircPostn depletion in the ventricular tissues of MI mice. Besides, the CircPostn depletion attenuated cardiomyocyte apoptosis in the mice. Mechanically, CircPostn served as a miR-96-5p sponge and miR-96-5p targeted BNIP3 in human cardiomyocytes, in which CircPostn up-regulated BNIP3 expression by targeting miR-96-5p. CircPostn promoted H/R-induced cardiomyocyte injury by modulating miR-96-5p/BNIP3 axis. Thus, we conclude that CircPostn contributes to MI-induced myocardial injury and cardiac remodeling by regulating miR-96-5p/BNIP3 axis. Our finding provides new insight into the mechanism by which CircPostn regulates MI-related cardiac dysfunction. CircPostn, miR-96-5p, and BNIP3 are potential targets for the treatment of MI-caused heart injury.